Ensino presencial e ensino não presencial: uma análise motivacional da disciplina de Química, subsidiada pela teoria da autodeterminação de alunos do ensino médio de uma escola pública do interior de Mato Grosso - Oliveira, Brenda Tavella (2021)
This dissertation presents a qualitative research that aimed to analyze the implications caused in the motivation of students with the changes in teaching formats in 2020, with students in the 1st year of high school and 2nd year of high school in a state school in a municipality in the interior of Mato Grosso, according to the theoretical contribution that supported the research called Theory of Self-Determination. For this, the Theory qualifies the motivational behaviors existing in a person, showing that it is possible to determine which motivational style is applied to the teaching of Chemistry, and whether it is possible to show whether the student has a greater tendency to demotivation, which consists of the lack of intention to action or extrinsic motivation, which is determined by the influence of the environment in which the student is and with degrees subdivided into regulations: external regulation; introjected regulation; identified regulation and integrated regulation. There is also intrinsic motivation, in which the “I” of the student guides their actions and is considered the most autonomous motivational style, involving the satisfaction of learning. The methodological course of this analysis was divided into two stages, the first referring to classroom teaching, experienced before the covid-19 pandemic was decreed. Data collection occurred through the on-line application of an opinion scale with the Lickert Scale of seven points and an open questionnaire, both constructed and guided by the assumptions of the Self-Determination Theory on the motivation of students during the Chemistry course. . The second stage also included data collection with an opinion scale and an open questionnaire, but referring to the modality of non-presential education, adopted during this pandemic context experienced in 2020. The analysis of the results was qualitative and showed low adherence to participate in the research for being an audience with different educational experiences developed during their school process. A general overview of the results obtained showed that many participants did not show lack of motivation as predominant, however, with the change in teaching, they showed a relative increase in lack of motivation. For the analysis of extrinsic motivation, the greatest demonstration was the change from more autonomous regulatory styles, in this case, identified and integrated regulation to more conditioned regulations, external regulation and introjected regulation and, in intrinsic motivation, even with a high degree in agreement with the statements, when relating this information with the answers to the open questionnaires, it could be seen that it was more the extrinsic motivation as predominant. Keywords: Discipline of Chemistry; Motivation and Pandemic covid-19.